The Concept of Creativity, the Essence of the Content and its Theoretical Methodological Foundations - Anvarovich, Nozimov Eldor (Research Parks Publishing LLC, 2023)
In this article, the concept of creativity, its essence and its theoretical and methodological foundations, human thinking, imagination, and the forms of thinking in it are explained. At the same time, the teacher's creativity and student's creative thingking are discussed.